(untitled) (Revista de Estudos Orientais, 2010)
This paper aims at showing the ethics of the intellectual and his testimony as a responsibility in front of Literature and History. As a support for this hypothesis, we will analyze The Kreutzer Sonata, by L. Tolstoy, and Summer in Baden-Baden, by L. Tsípkin.